Оцінка доробку Василя Доманицького-текстолога в українському літературознавстві - Цимбал, Б. (Літературознавчі обрії. Праці молодих учених, 2010)
The article examines evaluation of Vasyl’ Domanyts’kyi’s scholarly work as textologist by his contemporaries and present-day researchers. The study is conducted on the basis of the papers found in available periodicals and publiched separately. Ukrainian literary critics, while pointing out occasional mistakes in Domanyts’kyi’s research, nevertheless recognized the unquestionable importance of his textological papers and studies of Taras Shevchenko’s and Marko Vovchok’s writings.